(untitled) (Philological Studies, 2019)
The purpose of this paper is to establish why the same semantic features in newer lexemes are sometimes expressed as phrases and sometimes as compounds. The argument must be based on a structural-semantic and syntactic explanation, and the research findings can be applied to dictionary explanations of such newer lexicon.